A nomen novum for Protechinus Lavocat, 1961 (Mammalia, Erinaceidae), a junior homonym of the valid name Protechinus Noetling, 1897 (Echinoidea, Arbacioida) - Zijlstra, Jelle S. (Zootaxa, 2012)
Noetling (1897: 14) named the echinoid genus Protechinus from the Maastrichtian of Pakistan. Lambert (1898: 126) replaced the name Protechinus with a new name, Noetlingia, because Austin (1860: 446) had previously used the name Protoechinus for a different echinoid from the Carboniferous of Ireland. However, Noetlingia Lambert, 1898 is itself preoccupied by Noetlingia Hall & Clark, 1893, a brachiopod, and was accordingly replaced by Noetlingaster Vredenburg, 1911. Since then, Noetlingaster has been in general use for this genus (e.g., Mortensen 1940, Smith 1995).